Injury research : theories, methods, and approaches - Baker, Susan P.; Li, Guohua (Springer US, 2012)
Injury Research Theories, Methods, and Approaches   Guohua Li and Susan Baker, editors     From the long-held popular belief, "accidents will happen," it is now recognized that this needn't be the case. More and more, injury is being seen as no accident, not only predictable, but preventable-and an important public health issue requiring rigorous study and multiple levels of intervention.   To this end, Injury Research: Theories, Methods, and Approaches assembles a team of multidisciplinary experts from around the globe. Early chapters provide a solid foundation for gathering injury data and monitoring trends. Research methods and injury-reduction approaches gleaned from public health, medicine, engineering, behavioral science, and other areas demonstrate both the intricacies of causation and the potential for intervention. The result is an authoritative and comprehensive reference relevant across professional fields, geared toward fruitful collaborations. Injury Research is a bedrock text for graduate students and researchers in public health, medicine, biomechanical engineering, safety engineering, and behavioral science working in injury control, violence prevention, emergency medical services, trauma care, risk assessment, accident investigation and litigation, traffic safety, home safety, vehicle and product design, patient safety, health promotion, and public policy. Professionals working in health departments, the insurance sector, health economics, environmental engineering, civil engineering, urban planning, law enforcement, and criminal justice should find it important reading as well.